A phenomenological study examining how spirituality is manifested in the lives of student nurses whilst on clinical practice - Nunn, Stephanie (2009)
This study aims to identify how spirituality is manifested in the lives of student nurses whilst on clinical practice. The area of spirituality and spiritual care is becoming an important issue within nursing practice and there has been a significant amount of research into understanding spirituality and examining the views of healthcare professionals. However there is limited research in the student nurse perspective, justifying this study.